2012
DOI: 10.1186/1471-2105-13-139
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of classification algorithms for immunosignaturing data

Abstract: BackgroundHigh-throughput technologies such as DNA, RNA, protein, antibody and peptide microarrays are often used to examine differences across drug treatments, diseases, transgenic animals, and others. Typically one trains a classification system by gathering large amounts of probe-level data, selecting informative features, and classifies test samples using a small number of features. As new microarrays are invented, classification systems that worked well for other array types may not be ideal. Expression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 34 publications
0
24
0
2
Order By: Relevance
“…Previous studies indicated information content should peak between 20 and 100 features per disease 16 and the performance of linear classifiers tends to suffer as the total number of features increases 29 . The top 50 informative peptides and important sequence motifs are listed in Supplementary Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated information content should peak between 20 and 100 features per disease 16 and the performance of linear classifiers tends to suffer as the total number of features increases 29 . The top 50 informative peptides and important sequence motifs are listed in Supplementary Tables 1 and 2.…”
Section: Resultsmentioning
confidence: 99%
“…By using data from many features, immunosignatures can accommodate variations in the nondisease population, which may include an endemic population having substantial subclinical pathogen exposures. Analysis can be very basic, with statistical methods used to select features and probabilistic classifiers for class prediction (14).…”
mentioning
confidence: 99%
“…Such methods include t-tests [5], ANaYA [6], princi pal component analysis (PC A) [7]- [9], clustering [10]- [13], singular value decomposition (SYM) [14], and Naive Bayes approach [3]. In [9], sequence morphologies were used to determine latent relationships between various peptides and disease states.…”
Section: Introductionmentioning
confidence: 99%